Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1021/ac950410j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Enzyme-Linked Immunosorbent Assay for Determination of Polychlorinated Biphenyls in Environmental Soil and Sediment Samples

Abstract: An enzyme-linked immunosorbent assay (ELISA) for the quantitative determination of Aroclors 1242, 1248, 1254, and 1260 in soil and sediments was developed and its performance compared with that of gas chromatography (GC). The detection limits for Aroclors 1242 and 1248 in soil are 10.5 and 9 ng/g, respectively. The assay linear dynamic range is 50-1333 ng/g. Cross-reactivity of the assay with 37 structurally related potential cocontaminants in environmental soil samples was examined; none of the chlorinated an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 50 publications
(29 citation statements)
references
References 10 publications
1
28
0
Order By: Relevance
“…spiked}×100%]. It was observed that recoveries of added PCB from spiked soils by shaking with methanol were in the range 90.6-106.3%, in accordance with the results of Lawruk et al [1] and Johnson and Van Emon [8] who obtained recoveries of approximately 90%, irrespective of sample type and total Aroclor level.…”
Section: Evaluation Of Extraction By Shaking With Methanolsupporting
confidence: 86%
See 4 more Smart Citations
“…spiked}×100%]. It was observed that recoveries of added PCB from spiked soils by shaking with methanol were in the range 90.6-106.3%, in accordance with the results of Lawruk et al [1] and Johnson and Van Emon [8] who obtained recoveries of approximately 90%, irrespective of sample type and total Aroclor level.…”
Section: Evaluation Of Extraction By Shaking With Methanolsupporting
confidence: 86%
“…This might be a partial cause of the discrepancies between ELISA and GC results. The sample extraction procedure plays a major role in the overall analytical result even the accuracy and precision of ELISA for analysis of spiked samples are high [2,8,13]. The data obtained by Johnson and Van Emon [8] demonstrated that ELISA was capable of providing quantitative results for PCB when Soxhlet or supercritical-fluid extraction was used.…”
Section: Analysis Of Real Soil Samplesmentioning
confidence: 99%
See 3 more Smart Citations